Research on Immersive Experience Design and Tourist Perception of Smart Tourism from the Perspective of the Metaverse - Liu, Zhaojian; Huang, Liling (Pinnacle Academic Press Proceedings Series, 2026)
With the rapid rise and development of the metaverse, its integration with smart tourism has become a central focus of academic research and industry practice. The metaverse, characterized by virtual–real integration, immersion, interactivity, and persistence, offers unprecedented opportunities to reshape the design of immersive tourism experiences and to reconfigure how tourists perceive destinations, services, and value. This paper aims to systematically explore the key elements of immersive experience design in smart tourism from the perspective of the metaverse and to examine their impact on tourists’ cognitive, emotional, and behavioral perceptions. First, the study outlines the current status of the integration between the metaverse and smart tourism, summarizing typical application scenarios and technological pathways. Second, through literature review and case analysis, it identifies relevant theoretical foundations, including experience economy, presence, and technology acceptance, and constructs an analytical framework for metaverse-enabled tourism experiences. Third, the paper analyzes the main factors influencing tourist perception, such as immersion quality, interaction design, content authenticity, and virtual–real linkage, and discusses their implications for satisfaction, engagement, and intention to visit or revisit. Finally, based on empirical insights and best practices, the study proposes optimization strategies for destination managers and tourism enterprises in terms of experience planning, platform construction, content development, and governance. The findings enrich research on the metaverse and smart tourism and provide practical guidance for promoting innovative, high-quality development of the tourism industry.